Justice Sensitivity in Childhood and Adolescence. Issue 2 (12th October 2014) - Bondü, Rebecca; Elsner, Birgit
Abstract Individuals differ in their sensitivity toward injustice. Justice‐sensitive persons perceive injustice more frequently and show stronger responses to it. Justice sensitivity has been studied predominantly in adults; little is known about its development in childhood and adolescence and its connection to prosocial behavior and emotional and behavioral problems. This study evaluates a version of the justice sensitivity inventory for children and adolescents (JSI‐CA5) in 1472 9‐ to 17‐year olds. Items and scales showed good psychometric properties and correlations with prosocial behavior and conduct problems similar to findings in adults, supporting the reliability and validity of the scale. We found individual differences in justice sensitivity as a function of age and gender. Furthermore, justice sensitivity predicted emotional and behavioral problems in children and adolescents over a 1‐ to 2‐year period. Justice sensitivity perspectives can therefore be considered as risk and/or protective factors for mental health in childhood and adolescence.